Cultural Studies of LEGO
XIX, 357 p. 4 illus., 3 illus. in color.
Keywords: This collection examines LEGO from an array of critical and cultural studies approaches, foregrounding the world-renowned brand's ideological power and influence. Given LEGO’s status as the world’s largest toy manufacturer and a transnational multimedia conglomerate, Cultural Studies of Lego: More Than Just Bricks considers LEGO media's cultural messages; creativity with and within LEGO artifacts; and diversity within the franchise, including gender and race representation. The chapters’ in-depth analyses of topics including LEGO films, marketing tactics, play sets, novelizations, and fans offer compelling insights relevant to those interested in the LEGO brand and broader trends in the children’s popular culture market alike.